STRATEGI DINAS TENAGA KERJA DAN TRANSMIGRASI DALAM MENURUNKAN ANGKA PENGANGGURAN DI KABUPATEN SIAK TAHUN 2017-2020 - dayen iqwana (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2022)
This study aims to determine how the strategy of the Department of Manpower and Transmigration in Reducing Unemployment Rates in Siak Regency in 2017- 2020. The method used in this study is a descriptive study with a qualitative ap Retrieval of data and information obtained from information from informants, namely people who are considered to know and can be trusted in providing accurate information using two kinds of data, namely primary data and secondary data through interviews and documentation. The theoretical perspective used in this study is the theory of Strategic Management by Jack Koteen covering Corporate Strategy, Program Strategy, Resource Support Strategy, and Institutional Strategy. The results showed that the Strategy of the Manpower and Transmigration Office in Reducing Unemployment Rates in Siak Regency in 2017-2020 was mostly effective and running well. Based on the findings, the Manpower and Transmigration Office of Siak Regency increases competency-based job training and establishes cooperation with companies in the industrial business world, carries out job placement programs such as job fairs and training for job seekers at the Job Training Center (BLK) of Siak Regency. Resources in the form of budgets and seeking teaching staff who assist the implementation of the program as well as the use of social media.